PERBAIKAN PAKAN MEMANFAATKAN BAHAN LOKAL GUNA MENINGKATKAN PERTUMBUHAN AYAM KAMPUNG DI DUSUN KUSU-KUSU - Papilaya, Bercomien J; Rajab, Rajab (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Kampung chicken farms that are widely available in rural areas are generally traditional. The farmer's intervention in their maintenance is limited to ownership, simple cages and sometimes simple additional feed such as giving kitchen waste. The purpose of this activity is to increase the growth of free-range chickens and utilize local materials such as sago elastin, cassava leaves and earthworms. The target of implementing community service activities is breeders of free-range chicken business partners in Kusu-Kusu Hamlet. The methods used are lectures, discussions and training demonstrations on the processing and application of free-range chicken rations. The results showed that improving the ration with a nutritional composition of 17.83% crude protein, 6.37% crude fiber, 5.91% fat and 2873.012 Kcal metabolic energy could increase the free-range chicken body weight by 618.91 g, which was different than without application of science and technology of 359.00 grams, which is equal to 58.01%.